LIM1 contributes to the malignant potential of endometrial cancer - Kato, Hiroaki; Saeki, Noritaka; Imai, Matome; Onji, Hiroshi; Yano, Akiko; Yoshida, Shuhei; Sakaue, Tomohisa; Fujioka, Toru; Sugiyama, Takashi; Imai, Yuuki (Frontiers in Oncology, 2023)
Introduction The incidence of endometrial cancer (EC) has been increasing worldwide. However, because there are limited chemotherapeutic options for the treatment of EC, the prognosis of advanced-stage EC is poor. Methods Gene expression profile datasets for EC cases registered in The Cancer Genome Atlas (TCGA) was reanalyzed. Highly expressed genes in advanced-stage EC (110 cases) compared with early-stage EC (255 cases) were extracted and Gene Ontology (GO) enrichment analysis was performed. Among the enriched genes, Kaplan-Meier (KM) plotter analysis was performed. Candidate genes expression was analyzed in HEC50B cells and Ishikawa cells by RT-qPCR. In HEC50B cells, LIM homeobox1 (LIM1) was knocked down (KD) and cell proliferation, migration, and invasion ability of the cells were evaluated. Xenografts were generated using LIM1-KD cells and tumor growth was evaluated. Ingenuity Pathway Analysis (IPA) of RNA-seq data using LIM-KD cells was performed. Expression of phospho-CREB and CREB-related proteins were evaluated in LIM1-KD cells by western blotting and in xenograft tissue by immunofluorescent staining. Two different CREB inhibitors were treated in HEC50B and cell proliferation was evaluated by MTT assay. Results Reanalysis of TCGA followed by GO enrichment analysis revealed that homeobox genes were highly expressed in advanced-stage EC. Among the identified genes, KM plotter analysis showed that high LIM1 expression was associated with a significantly poorer prognosis in EC. Additionally, LIM1 expression was significantly higher in high-grade EC cell lines, HEC50B cells than Ishikawa cells. Knockdown of LIM1 showed reduced cell proliferation, migration and invasion in HEC50B cells. Xenograft experiments revealed that tumor growth was significantly suppressed in LIM1-KD cells. IPA of RNA-seq data using LIM-KD cells predicted that the mRNA expression of CREB signaling-related genes was suppressed. Indeed, phosphorylation of CREB was decreased in LIM1-KD cells and LIM1-KD cells derived tumors. HEC50B cells treated by CREB inhibitors showed suppression of cell proliferation. Conclusion and discussion Collectively, these results suggested that high LIM1 expression contributed to tumor growth via CREB signaling in EC. Inhibition of LIM1 or its downstream molecules would be new therapeutic strategies for EC.